Contextual Meaning Analysis of Narrative Texts in The 10th-Grade English Textbook Siap Merdeka Belajar Bahasa Inggris - Syifa Kamilah Nur-Aqidah; Yayan Suryana; Nida Amalia Asikin (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2025)
This study aims to analyze the contextual meanings found in three narrative texts—Timun Mas, The Two Elves, and Titanic—from the 10th-grade English textbook SIAP Merdeka Belajar Bahasa Inggris. Based on Mansoer Pateda’s (2010) theory of contextual meaning, this study identifies and interprets eleven types of contextual meaning: Personal Context, Situational Context, Purposive Context, formal or informal context, Mood Context, Context of Time, Context of Place, Object Context, Completeness of Context, Linguistic Context, and Language Context. A descriptive qualitative method was employed, with data gathered from selected narrative texts in the textbook. The analysis involved the stages of data reduction, data verification, and drawing conclusions. The findings revealed that all three texts contained multiple types of contextual meaning, with situational and Mood Context being the most frequently identified across the texts. The analysis shows that understanding contextual meaning is essential for interpreting narratives deeply, as meaning is influenced by characters' identities, emotional states, intentions, cultural background, and narrative settings. This research contributes to the semantic study of English learning materials and highlights the value of context-based interpretation in narrative comprehension. Keywords: semantics, contextual meaning, narrative texts, English textbook